1990
DOI: 10.1111/j.1365-2761.1990.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral vaccination against vibriosis in turbot, Scophthalmus maximus (L.), and sea bass, Dicentrarchus labrax (L.)

Abstract: Turbot, Scophthalmus maximus (L.), and sea bass, Dicentrarchus labrax (L.), are susceptible to vibriosis. a septicaemia caused in France by Vibrio anguillarum 408. A bacterin produced with this strain by Rhone-Mcrieux has been tested orally in both species and, as a con\parison, by intraperitoneal injection. During a ehallenge carried out 4 weeks later by intraperitoneal inoculation, the protection observed in orally vaccinated fishes was significant (72 % in sea bass and 70 % in turbot). Eleven weeks after va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…These results suggest the formation of systemic memory in both species after oral vaccination with a bioencapsulated bacterin. In the case of vaccination against V. anguillarum, the humoral response is strongly related to final protection against vibriosis (Viele et al, 1980;Harrel et al, 1975;Dec et al, 1990). In addition, a mucosal immune response resulting in specific antibodies at mucosal surfaces may also be induced after oral vaccination (Rombout et al, 1989c) and could contribute to a higher level of protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest the formation of systemic memory in both species after oral vaccination with a bioencapsulated bacterin. In the case of vaccination against V. anguillarum, the humoral response is strongly related to final protection against vibriosis (Viele et al, 1980;Harrel et al, 1975;Dec et al, 1990). In addition, a mucosal immune response resulting in specific antibodies at mucosal surfaces may also be induced after oral vaccination (Rombout et al, 1989c) and could contribute to a higher level of protection.…”
Section: Discussionmentioning
confidence: 99%
“…However, till now oral immunisation of fish has not been very successful (Ellis, 1988). Compared with injection or immersion methods lower protection and/or lower antibody levels in serum were observed (Amend & Johnson, 1981;Johnson & Amend, 1983;Rombout et al, 1986;Dec et al, 1990) and large quantities of bacterin are required to be e#ective (Ward, 1982;Ellis, 1988). On the other hand, Johnson & Amend (1983) showed that anal vaccination against vibriosis and yersiniosis resulted in good protection, while oral vaccination only gave a limited protection.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of oral and rectal vaccination trials and the protection induced by passive immunization with serum from orally vaccinated fish are supportive for such as systemic immune response (Kawai e t al. 1981, Dec et al 1990, Vigneulle 1990). …”
Section: Discussionmentioning
confidence: 99%
“…In marine fish species, good protection has been observed following oral immunization of turbot (Baudin Laurencin & Batellier 1986) and seabass (Dec et al 1990). In salmonids, oral immunization has yielded variable results: it resulted in good protection in the studies of Johnson & Amend (1983) and Vigneulle (1990), but it proved ineffective in studies reported by Baudin Laurencin & Tangtrongpiros (1980) and Horne et al (1982).…”
Section: Introductionmentioning
confidence: 99%
“…The use of vaccines in aquaculture has been shown to successfully protect fish against bacterial diseases, such as vibriosis (caused by Listonella anguillarum [formerly Vibrio anguillarum] and V. ordalii ), edwardsiellosis, furunculosis, streptococcosis and pasteurellosis (Song et al 1982, Austin 1983, Larsen 1988, Smith 1988, Dec et al 1990, Roogers & Xu 1992, Magariños et al 1994, Quentel & Ogier de Baulny 1995, Toranzo et al 1995, Romalde et al 1996, Gravningen et al 1998. In particular, the success achieved in immunization against other vibrioses (Smith 1988) suggests that the best solution would be an effective vaccine against V. vulnificus.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%